Validity and Normative Data for the Biber Figure Learning Test: A Visual Supraspan Memory Measure. (September 2020) - Gifford, Katherine A.; Liu, Dandan; Neal, Jacquelyn E.; Acosta, Lealani Mae Y.; Bell, Susan P.; Wiggins, Margaret E.; Wisniewski, Kristi M.; Godfrey, Mary; Logan, Laura A.; Hohman, Timothy J.; Pechman, Kimberly R.; Libon, David J.; et al.
The Biber Figure Learning Test (BFLT), a visuospatial serial figure learning test, was evaluated for biological correlates and psychometric properties, and normative data were generated. Nondemented individuals ( n = 332, 73 ± 7, 41% female) from the Vanderbilt Memory & Aging Project completed a comprehensive neuropsychological protocol. Adjusted regression models related BFLT indices to structural brain magnetic resonance imaging and cerebrospinal fluid (CSF) markers of brain health. Regression-based normative data were generated. Lower BFLT performances (Total Learning, Delayed Recall, Recognition) related to smaller medial temporal lobe volumes and higher CSF tau concentrations but not CSF amyloid. BFLT indices were most strongly correlated with other measures of verbal and nonverbal memory and visuospatial skills. The BFLT provides a comprehensive assessment of all aspects of visuospatial learning and memory and is sensitive to biomarkers of unhealthy brain aging. Enhanced normative data enriches the clinical utility of this visual serial figure learning test for use with older adults.